Acute Liver Failure in a Pediatric Patient with Tetralogy of Fallot following Cardiac Catheterization. (26th July 2020) - Salik, Irim; Easwar, Jasmeet; Jacoby, Michael
Abstract : A 4-month-old female with Tetralogy of Fallot (TOF) developed acute liver failure (ALF) following a cardiac catheterization procedure to correct severe stenosis of her right ventricular outflow tract (RVOT) conduit via balloon angioplasty. Cardiac history included TOF, heterotaxy syndrome, ipsilateral pulmonary veins, interrupted inferior vena cava (IVC) with azygos continuation, patent ductus arteriosus (PDA), and pulmonary atresia that was repaired with a right ventricle (RV) to pulmonary artery (PA) conduit. This is the first case described of its kind to our knowledge. Consent was obtained from the patient's family to publish this case report.